Involvement of aryl hydrocarbon receptor in the cytotoxicity of corannulene and its derivatives. (15th March 2020) - Li, Gentao; Ma, Ruicong; Xing, Yufeng; Wei, Jing; Bi, Yajuan; Li, Caiyu; Xiong, Hui; Baldridge, Kim K.; Huang, Jianhui; Siegel, Jay S.; Zhang, Youcai
Highlights: COR causes less cytotoxic responses than benzo[a]pyrene in hepatoma cells. COR is a weak inducer of aryl hydrocarbon receptor (AhR). AhR mediates the induction of cytochrome P450 1 isozymes by COR. Derivatization alters the cytotoxicity of COR and its binding with AhR. Abstract: Despite numerous studies on the toxicities of planar polycyclic aromatic hydrocarbons (PAHs), very little is known about the toxicological profiles of non-planar PAHs. In the present study, the cytotoxicity of corannulene (COR), a typical bowl-shaped PAH with a myriad of applications in the area of material chemistry, and benzo[a]pyrene (BaP), a typical planar PAH with similar molecular weight, were systematically compared in various cell lines. Compared with BaP, exposure to COR resulted in less cytotoxic responses in both human (HepG2) and murine (Hepa1-6) hepatoma cells, which was characterized with a slower cellular accumulation as well as a weaker induction of cytochrome P450 1 (CYP1/Cyp1) isozymes. Knockdown of aryl hydrocarbon receptor (AhR) by siRNA attenuated the inductive effect of COR on CYP1A/Cyp1a mRNA levels in these two cell lines. Further analysis revealed that derivatization greatly influenced the cytotoxicity of COR, which was positively correlated with their binding affinities to the AhR, as demonstrated by in silico molecular docking. Overall, these results suggest that AhR appears to be involved in the cytotoxic responses of COR and its derivatives, providing a fundamental understanding of the biological effects of bowl-like PAHs.